Kebijakan Hukum Pidana dalam Penanganan Tindak Pidana Khusus Narkotika dan Dampak Sosialnya Bagi Masyarakat Indonesia (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This research examines criminal law policy in handling special narcotics crimes and their social impacts on Indonesian society. Narcotics crime constitutes an extraordinary crime that threatens public health, security, and social resilience. Therefore, the state implements criminal law policies through penal and non-penal approaches regulated in statutory provisions, particularly the Narcotics Law. This research aims to analyze the effectiveness of criminal law policies in combating narcotics crimes and to examine the social impacts arising from the implementation of such policies. The research method used is normative legal research employing statutory and conceptual approaches. The findings indicate that criminal law policies in narcotics control still face various challenges, including ineffective law enforcement, prison overcapacity, and social stigma against narcotics users. The social impacts are not only experienced by offenders but also affect families and the wider community. Consequently, criminal law policies that prioritize restorative justice, rehabilitation, and preventive measures are urgently needed to reduce negative social impacts and to ensure sustainable protection for society in Indonesia.